Mapping research on the application of magnetic particles in the removal of oil in water: analysis of research between 2000 and 2018 (Research, Society and Development, 2019)
The demand for technologies aimed at treating effluents containing emulsified oil or accidents with oil spills is increasing. Therefore, the use of nanotechnologies has been constantly addressed in order to solve such problems. Magnetite has generally been used as magnetic substrate because of its low cost and cytotoxicity. In order to evaluate the progress of the researches to use Fe3O4 to remove emulsified oil, a bibliometric revision was carried out using the Web of Science platform. Based on the data obtained after the refinement of the research, it has been observed that studies aimed at this area are few, but the results have shown promise.